Biocompatible polypeptide nanogel: Effect of surfactants on nanogelation in inverse miniemulsion, in vivo biodistribution and blood clearance evaluation - Oleshchuk, Diana; Šálek, Petr; Dvořáková, Jana; Kučka, Jan; Pavlova, Ewa; Francová, Pavla; Šefc, Luděk; Proks, Vladimír (Materials science & engineering. C, Materials for biological applications, 2021)
Horseradish peroxidase (HRP)/H2O2-mediated crosslinking of polypeptides in inverse miniemulsion is a promising approach for the development of next-generation biocompatible and biodegradable nanogels. Herein, we present a fundamental investigation of the effects of three surfactants and their different concentrations on the (HRP)/H2O2-mediated nanogelation of poly[N5-(2-hydroxyethyl)-l-glutamine-ran-N5-propargyl-l-glutamine-ran-N5-(6-aminohexyl)-l-glutamine]-ran-N5-[2-(4-hydroxyphenyl)ethyl)-l-glutamine] (PHEG-Tyr) in inverse miniemulsion. The surfactants sorbitan monooleate (SPAN 80), polyoxyethylenesorbitan trioleate (TWEEN 85), and dioctyl sulfosuccinate sodium salt (AOT) were selected and their influence on the nanogel size, size distribution, and morphology was evaluated. The most effective nanogelation stabilization was achieved with 20 wt% nonionic surfactant SPAN 80. The diameter of the hydrogel nanoparticles was 230 nm (dynamic light scattering, DLS) and was confirmed also by nanoparticle tracking analysis (NTA) which showed the diameters ranging from 200 to 300 nm. Microscopy and image analyses showed that the nanogel in the dry state was spherical in shape and had number-average diameter Dn = 26 nm and dispersity Ð = 1.91. In the frozen-hydrated state, the nanogel appeared porous and was larger in size with Dn = 182 nm and Ð = 1.52. Our results indicated that the nanogelation of the polymer precursor required a higher concentration of surfactant than classical inverse miniemulsion polymerization to ensure effective stabilization. The developed polypeptide nanogel was radiolabeled with 125I, and in vivo biodistribution and blood clearance evaluations were performed. We found that the 125I-labeled nanogel was well-biodistributed in the bloodstream, cleared from mouse blood during 48 h by renal and hepatic pathways and did not provoke any sign of toxic effects.
Keywords: povrchově aktivní látky; Surface-Active Agents; Inverse miniemulsion; Nanogels; Blood clearance; tkáňová distribuce; zvířata; myši; Surfactant; Polyethylene Glycols; peptidy; Mice; Peptides; nanogely; peroxid vodíku; Polyethyleneimine; Nanogel; Polypeptide; in vivo biodistribution; Animals; polyethylenglykoly; Hydrogen Peroxide; polyethylenimin; Tissue Distribution